RGD‐functionalized supported lipid bilayers modulate pre‐osteoblast adherence and promote osteogenic differentiation. Issue 4 (8th January 2020) - Verstappen, Johanna F. M.; Jin, Jianfeng; Koçer, Gülistan; Haroon, Mohammad; Jonkheijm, Pascal; Bakker, Astrid D.; Klein‐Nulend, Jenneke; Jaspers, Richard T.
Abstract: Biomaterial integration into bone requires optimal surface conditions to promote osteoprogenitor behavior, which is affected by integrin‐binding via arginine‐glycine‐aspartate (RGD). RGD‐functionalized supported lipid bilayers (SLBs) might be interesting as biomaterial coating in bone regeneration, because they allow integration of proteins, for example, growth factors, cytokines, and/or antibacterial agents. Since it is unknown whether and how they affect osteoprogenitor adhesion and differentiation, the aim was to investigate adhesion, focal adhesion formation, morphology, proliferation, and osteogenic potential of pre‐osteoblasts cultured on RGD‐functionalized SLBs compared to unfunctionalized SLBs and poly‐l ‐lysine (PLL). After 17 hr, pre‐osteoblast density on SLBs without or with RGD was similar, but lower than on PLL. Cell surface area, elongation, and number and size of phospho‐paxillin clusters were also similar. Cells on SLBs without or with RGD were smaller, more elongated, and had less and smaller phospho‐paxillin clusters than on PLL. OPN expression was increased on SLBs with RGD compared to PLL. Moreover, after 1 week, COL1a1 expression was increased on SLBs without or with RGD. In conclusion, pre‐osteoblast adhesion and enhanced differentiation were realized for the first time on RGD‐functionalized SLBs, pointing to a new horizon in the management of bone regeneration using biomaterials. Together with SLBs nonfouling nature and the possibility of adjusting SLB fluidity and peptide content make SLBs highly promising as substrate to develop innovative biomimetic coatings for biomaterials in bone regeneration.